2016
DOI: 10.1180/claymin.2016.051.2.07
|View full text |Cite
|
Sign up to set email alerts
|

Effect of layer charge on the crystalline swelling of Na+, K+ and Ca2+ montmorillonites: DFT and molecular dynamics studies

Abstract: The swelling and cation exchange properties of montmorillonite are fundamental in a wide range of applications ranging from nanocomposites to catalytic cracking of hydrocarbons. The swelling results from several factors and, though widely studied, information on the effects of a single factor at a time is lacking. In this study, density functional theory (DFT) calculations were used to obtain atomic-level information on the swelling of montmorillonite. Molecular dynamics (MD) was used to investigate the swelli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 30 publications
4
11
0
Order By: Relevance
“…The pictorial diagram about the coordination number and Van der Waals radius of Na + are shown in Figure 13. This research result is in line with the conclusions acquired by Sun et al and Seppälä et al [6,50]. Besides, the strength of the main peak of the g(Na-Ow) increases gradually with the decrease of layer charge density.…”
Section: The Rdf Of Na-o Wsupporting
confidence: 92%
“…The pictorial diagram about the coordination number and Van der Waals radius of Na + are shown in Figure 13. This research result is in line with the conclusions acquired by Sun et al and Seppälä et al [6,50]. Besides, the strength of the main peak of the g(Na-Ow) increases gradually with the decrease of layer charge density.…”
Section: The Rdf Of Na-o Wsupporting
confidence: 92%
“…It follows that Ca 2+ released from the MK solution was consumed entirely during the process of cationic exchange between the soil solution and montmorillonite exchangeable sites at OMC. The newly released alumina did not exercise any major impact on the diffraction pattern of montmorillonite in the soil treated with MKG, which is in line with the current experimental and modeling studies favoring the major impact of the nature and type of interlayer cations, as well as their hydration states, on XRD intensities of clay minerals [34,35]. XRD reflexes of quartz showed reduced intensities following the addition of MKG and FAG in OMC and saturation conditions compared to the natural soil (Figures 4 and 5).…”
Section: Mineralogy Of Natural and Treated Soilssupporting
confidence: 88%
“…Similar swelling behavior with increasing layer charge due to the significant number of interlayer cations and greater ion hydration enthalpies was reported by Yi et al (2018). Even so, opposite claims were made by Greathouse and Sposito (1998) and Seppälä et al (2016). They indicated that Mt with lower layer charges experiences more significant swelling than one with a higher charge.…”
Section: Effect Of Layer Charge and Charge Substitution Sitessupporting
confidence: 52%
“…However, Tao et al (2010) showed that Na-Mt overall swelling was higher than that of Ca-Mt and K-Mt. Still, however, it is essential to note that the higher the valence, the higher the cation's hydration energy (Hensen et al 2001;Li et al 2019;Seppälä et al 2016).…”
Section: Effect Of Type Of Interlayer Cationmentioning
confidence: 99%